Sub-Saharan Employment Developments : The Important Role of Household Enterprises with an Application to Rwanda - Thomas, Alun (IMF Working Papers; Working Paper ;, 2015)
This paper documents the structural transformation in employment that has taken place in Sub-Saharan Africa (SSA) over the past 15 years. In contrast to Asian economies, where at least half of the labor flows out of agriculture have gone into industry, in SSA, most of the workers have ended up in the service sector, especially household enterprises. Rwanda has been one of the stellar performers in SSA in terms of structural transformation with the strongest movement of workers out of agriculture. Contrary to conventional wisdom, except for the very top of the distribution of consumption in Rwanda, families in household enterprises now consume as much as non-agricultural wage earners.